2013
DOI: 10.1073/pnas.1221255110
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin alters serum vitamin D metabolite and fibroblast growth factor 23 concentrations and the urinary excretion of calcium

Abstract: Inactivating mutations of the SOST (sclerostin) gene are associated with overgrowth and sclerosis of the skeleton. To determine mechanisms by which increased amounts of calcium and phosphorus are accreted to enable enhanced bone mineralization in the absence of sclerostin, we measured concentrations of calciotropic and phosphaturic hormones, and urine and serum calcium and inorganic phosphorus in mice in which the sclerostin (sost) gene was replaced by the β-D-galactosidase (lacZ) gene in the germ line. Knocko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
84
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 52 publications
(35 reference statements)
12
84
2
3
Order By: Relevance
“…PHEX снижает FGF-23. Вероятно, склеростин ингибирует PHEX и изменяет про-цессинг FGF-23 [58]. Склеростин и FGF23 могут синхрон-но действовать на почечные канальцы для повышения экскреции кальция и фосфора с мочой, тем самым сни-жая доступность этих элементов для минерализации.…”
Section: изучение маркеров костного ремоделирования при сахарном диабетеunclassified
“…PHEX снижает FGF-23. Вероятно, склеростин ингибирует PHEX и изменяет про-цессинг FGF-23 [58]. Склеростин и FGF23 могут синхрон-но действовать на почечные канальцы для повышения экскреции кальция и фосфора с мочой, тем самым сни-жая доступность этих элементов для минерализации.…”
Section: изучение маркеров костного ремоделирования при сахарном диабетеunclassified
“…While PTH and 1a,25(OH) 2 D decrease fractional excretion of calcium by increasing the efficiency of calcium reabsorption in the DT, sclerostin increases fractional excretion of calcium (the absence of sclerostin expression being associated with a reduced fractional excretion of calcium). 6 Thus, the scheme of adaptations to reductions in calcium intake and resultant downstream alterations in hormones (see Figure 1B for current understanding) may need to be amended to include changes in sclerostin expression (Figure 4). In the modified scheme, reduced sclerostin expression, which result from increases in PTH, [126][127][128][129] effect on Cyp27b1 expression since FGF-23 concentrations are diminished in Sost 2/2 mice along with an increase in serum P i concentrations.…”
Section: Overview Of Calcium Homeostasismentioning
confidence: 99%
“…In the modified scheme, reduced sclerostin expression, which result from increases in PTH, [126][127][128][129] effect on Cyp27b1 expression since FGF-23 concentrations are diminished in Sost 2/2 mice along with an increase in serum P i concentrations. 6 The bonederived FGF-23 is a known suppressor of 25(OH)D-1a-hydroxylase, 116 suggesting that the increase in 1a,25(OH) 2 D concentrations in the absence of sclerostin may have resulted from lower FGF-23 levels. In other words, sclerostin may stimulate FGF-23 release from bone, which suppresses renal 1a,25(OH) 2 D synthesis.…”
Section: Overview Of Calcium Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Geriatrics lacking calcium for long time may have some symptoms, such as premature gomphiasis, teeth obscission, obvious hunchback, height decrease, pain in lumbar spine and cervical spine, constipation, hyposomnia [5,6]. Urinary calcium level (UCL) can reflect the calcium metabolism and bone status [7,8]. Many studies have reported that an increased intake of dietary calcium or a highdairy diet may reduce inflammation, oxidative stress, particularly in over-weighted people, through promoting lipid metabolism and a loss of body fat [3,9].…”
Section: Introductionmentioning
confidence: 99%